Non‐invasive assessment of cardiac output at rest and during exercise by finger plethysmography. (3rd April 2013) - Critoph, Christopher H.; Patel, Vimal; Mist, Bryan; Thomas, Martin D.; Elliott, Perry M.
Summary Aims We sought to determine the accuracy of finger plethysmography using pulse waveform analysis with brachial calibration for measurement of cardiac output during submaximal exercise by comparing it against an acetylene (C2H2) uptake technique. Methods The study included 24 healthy volunteers (12 males, age 35 ± 8 years). Testing was performed on an upright cycle ergometer using an incremental protocol. Cardiac output measurements were performed at rest and during sub‐maximal exercise using a single breath C2H2 uptake technique and continuously using finger plethysmography with brachial calibration. Results Valid results at rest and during sub‐maximal exercise were achieved in 20 of 24 participants. Cardiac output at rest was 5·3 ± 1·1 and 5·2 ± 1·2 l min−1 for finger plethysmography and C2H2, respectively, P = 0·712. Mean difference between techniques was −0·1 ± 0·5 l min−1. Cardiac output during submaximal exercise was 10·2 ± 2·3 and 10·3 ± 2·1 l min−1 for finger plethysmography and C2H2, respectively, P = 0·898. Mean difference between techniques was 0·1 ± 1·5 l min−1. The overall correlation between finger plethysmography and C2H2 data obtained during rest and exercise was r2 = 0·872, P<0·0001. Mean rise in cardiac output during exercise was 4·9 ± 1·5 (finger plethysmography) and 5·1 ± 1·5 l min−1 (C2H2), P = 0·64. Conclusion Finger plethysmography determined cardiac output values both at rest and during sub‐maximal exercise are comparable with those obtained using a single breath C2H2 uptake technique.